2008
DOI: 10.1007/s00265-008-0581-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of the queen mandibular gland pheromone in honeybees (Apis mellifera): honest signal or suppressive agent?

Abstract: Queen pheromones interfere with worker reproduction in social insects. However, there is still an unresolved question as to whether this pheromone acts as an "honest" signal for workers, giving a reliable indication of the queen's reproductive value, or as a suppressive agent, inhibiting worker reproduction independent of the queen's reproductive capacity. In honeybees (Apis mellifera), the queen's mandibular gland secretion, a mix of fatty acids and some aromatic compounds, is crucial for regulating the repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 48 publications
5
64
0
2
Order By: Relevance
“…dishonest, queen control. For example, the relative proportion of 9-ODA in the mandibular gland secretion was lower in highly fecund, mated honeybee queens than in both sterile and egg-laying virgin queens, and a multivariate analysis of all compounds did not separate fertile unmated and mated queens (Strauss et al, 2008). Likewise, the proportion of 3,11-dimethylheptacosane increased with the fecundity of both mated queens and unmated workers of P. inversa (d'Ettorre et al, 2004), and 9-hentriacontene also increased when unmated workers of D. quadriceps achieved social and reproductive dominance .…”
Section: Correlations Between Fecundity and Chemical Compoundsmentioning
confidence: 99%
“…dishonest, queen control. For example, the relative proportion of 9-ODA in the mandibular gland secretion was lower in highly fecund, mated honeybee queens than in both sterile and egg-laying virgin queens, and a multivariate analysis of all compounds did not separate fertile unmated and mated queens (Strauss et al, 2008). Likewise, the proportion of 3,11-dimethylheptacosane increased with the fecundity of both mated queens and unmated workers of P. inversa (d'Ettorre et al, 2004), and 9-hentriacontene also increased when unmated workers of D. quadriceps achieved social and reproductive dominance .…”
Section: Correlations Between Fecundity and Chemical Compoundsmentioning
confidence: 99%
“…Restricting the queen to one half of the hive limits the amount of comb available for her to lay eggs in, resulting in reduced amounts of brood in our excluder colonies. In A. mellifera there is a clear relationship between ovary activation and the amount of brood present; workers will activate their ovaries when the amount of brood present decreases (Mohammedi et al, 1996, Mohammedi et al, 1998, Oldroyd et al, 2001b, Pettis et al, 1997, Strauss et al, 2008. In addition, studies of A. mellifera have shown that a decrease in the amount of young brood present in colonies induces queen supersedure (Pettis et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Worker ovarian development is rare or absent in the presence of QMP (Hoover et al, 2003, Butler andFairey, 1963); however, the precise effect of QMP is taxonomically variable (Hoover et al, 2003, Wossler andCrewe, 1999). While workers interpret the presence of QMP as a signal of the queen's presence, they assess the fertility of the queen via signals emanating from the brood (Mohammedi et al, 1996, Mohammedi et al, 1998, Oldroyd et al, 2001b, Strauss et al, 2008. If the queen stops producing eggs, either because she is ailing or no longer present, the strength of the brood signal will decrease, eventually resulting in queen-supersedure (Pettis et al, 1997).…”
Section: Other Means Of Regulation Of Worker Reproduction In Queenrigmentioning
confidence: 99%
See 1 more Smart Citation
“…QMP is dominated by the compound of 9-ODA, the so-called queen substance, which is essential for the inhibition of ovary activation and egg-laying behavior in workers (Hoover et al 2003;Dietemann et al 2007;Strauss et al 2008). Anarchistic workers are less inhibited by the queen pheromones than wild-type workers, and it has been suggested that this is due to a reduced sensitivity to queen-and larvae-produced signals Hoover et al 2005b).…”
Section: Introductionmentioning
confidence: 99%